Performance budgeting in the South-East Europe countries: A comparative study on present state and future perspectives - Meldina Kokorović Jukan; Elman Nadžaković (Economic Review: Journal of Economics and Business, 2022)
Adoption of any budget is perhaps the most important and time-consuming activity of any government. As a modern tool for linking strategic planning and budgeting, performance budgeting is conditio sine qua non for implementation of modern multi-annual budgeting system. Performance budgeting was first introduced in the United States and today different models are used in practice. The aim of this research is to investigate the state of implementation of performance budgeting reform(s) in the South East Europe (SEE) countries, namely Albania, Kosovo, Montenegro, North Macedonia, Serbia, Bosnia and Herzegovina, Bulgaria, Croatia, Moldova, Romania, Greece, Slovenia, and Turkey and their struggle to implement performance budgeting reform. The United States, Australia and the European Union are the examples of developed countries implementing performance-based budgeting and their experience can be helpful to SEE countries in their efforts to establish working performance budgeting system. In this research, the focus is on answering questions about presence and elements of national performance framework, UN Sustainable Development Goals, performance budgeting framework and characteristics, and authority for the design and implementation of performance budgeting system. Based on the research results, the authors provide recommendations for better implementation of performance budgeting in selected countries.
Keywords: H61; H53; I38; 330; Budget; Performance budgeting; South East Europe